A new species of predaceous midge in the Patagonian genus Austrosphaeromias with a redescription of A. chilensis (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2015)
A new species of predaceous midge, Austrosphaeromias setosa sp. nov., is described and illustrated from adult males and females collected in the Patagonian-Andean region of Argentina and Chile. Based on examination of the type species of Austrosphaeromias Spinelli, 1997 and recently collected specimens from near the type-locality, the female and previously unknown male of Austrosphaeromias chilensis (Ingram & Macfie, 1931) are also described and illustrated. Descriptions are accompanied by color photographs and illustrations of key features of females and males of both species. We also provide a key to adult females and males of the four species of Austrosphaeromias.